Emerging patterns and behaviors in a green resilient economy - Andrei, Jean Vasile; Grigorescu, Adriana (Lab for entrepreneurship and development., 2024)
The COVID-19 outbreak aggravated recurrent economic issues and problems of developing a resilient economy and technological development inequality between entities, countries, production structure, unemployment and social disorders that have resulted in the accentuating of political, economic, business and trade relations. Resilient economies, technological development and green entrepreneurship in the New Normal present opportunities and challenges in achieving a balanced transition. Emerging Patterns and Behaviors in a Green Resilient Economy provides a comprehensive and nuanced understanding of contemporary green entrepreneurship, highlighting areas that need more exploration and encouraging new, innovative solutions to the challenges faced in creating a sustainable economy. Lab for Entrepreneurship and Development is Emerald's innovative book series on the study of entrepreneurship and development, striving to set the agenda for advancing research on entrepreneurship in the context of finance, economic development, innovation, and the society at large.